A Comparative Study of Effect of pH and Phosphate Buffer on Adsorption of Phenols on Filtrasorb-300 - SHASTRI, S.S.; BHAKE, A.B. (Asian Journal of Chemistry, 2010)
Increasing environmental awareness and concern are bound to expand the role of activated carbon as a highly efficient and broad spectrum technology for the removal of organic pollutants from aqueous waste. Adsorption equilibrium and kinetics of some priority pollutants were studied on Filtrasorbs-300 at 30oC. The effect of various physico-chemical parameters associated with both absorbent and adsorbate on the adsorption rate and equilibrium were investigated. A batch reactor was selected for the evaluation and kinetic data. The adsorption data were analysed by Langmuir and B.E.T. isotherm equation and the rate of removal of adsorbate was calculated from the kinetic data by using a simplified rate expression based on Langmuir theory. All the adsorbates were analysed by UV absorption spectrophotometry.